PREOPERATIVE PLANNING USING MEDICAD SOFTWARE (GERMANY) - Petar Angelov; Andrey Iotov (Journal of the Bulgarian Orthopaedics and Trauma Association, 2023)
Preoperative planning is an important step in preparing for total hip arthroplasty. Digital preoperative planning allows the surgeon to select templates and overlay them electronically on the image. This way, the necessary measurements of the dimensions of the implants, the position of the implants, and the restoration of the biomechanics are carried out. Digital templating is becoming the preferred method for preoperative planning in total hip arthroplasty (THA). New technologies reduce inconsistencies and errors can be minimized. Our experience with the MediCAD software has shown that its accuracy is within +/- 1 size in 85% of acetabular component placements and 82% of femoral component placements. These results are comparable to those reported in the literature to date.